The Acquisition Of Implicature Of A Four Years Old Child - Masruroh, Aeni; Arilesa, Rini; Magria, Vera (Universitas Muara Bungo, 2025)
The several points of this research are the kind of implicature, the process acquired in a 4-year-old child, and the function of language in implicature. The purpose of this research is to find out the kind of implicature in conversation, to find out how the process of acquiring implicature for a four-year-old child, and to determine the function of language in implicature. The researcher uses the descriptive qualitative method to do the research. While analyzing the datum, the researcher used theory by Grice (1975) to find out the kind of implicature, Chomsky (1957) to find out how the process is acquired in the implicature of a four-year-old child, and Searle (1979) to find out the function of language in implicature. Data were collected using the Participant Observation Technique (SLC) method by Sudaryanto (1993). In addition, to support this method, the researcher also uses the note-taking technique, or what is commonly called the Decisive Element Sorting Technique (DES). The object of the research in this thesis has reached the Explosion Stage, where at that stage children are able to create utterance implicature. As a result, in this thesis there are 11 data as conversational implicature and there are 4 datum as conventional implicature, so in all the datum there are 15 datum. In the violation maxim found in the research datum in this thesis, there are 3 maxims of quality, 3 maxims of quantity, 8 maxims of manner, and the last is 1 maxim of relation / relevance. Then some of the functions of language contained in the data analysis in this thesis are 8 functions of language as expressive, 3 function of language as directive, 1 function of language as declarative, and 3 function of language as assertive.